Pediculosis pubis - Chang Patricia (Our Dermatology Online, 2011)
We report a male patient of 24 years old with itching at groin and pubis. Pubic hair test showed the presence of lices (fig.2-4).Pediculosis is an infestation of man and animals by insects Anoplura (Lice) Vampire ectoparasites. It´s important poor hygiene, promiscuity, fomites, sexual transmission. Etiology: Pediculus humanus capitis, Human Pediculus corporis, Phthirus pubis or pubic lice. Clinically pediculosis can be classify in :head lice, body lice, pubic pediculosis. Phthirus pubis or crab lice is the agent of pediculus pubis, the sites affected are pubic region other sites as thighs, trunk, armpit, eyebrows, eyelashes, beard and scalp. Pruritus hematic crusts, excoriations, stains 0.5 cm -1 blue cerulean spots may be associated with other STD. The diagnosis is based in the clinical aspect and observes the parasite. Phthirus short pubis or pubic lice parasite, it´s size: 0.8-1.2 mm his first legs resemble those of a crab with sucking, slow walking 10 cm / min. Treatment is based on head lice or nits destruction benzyl benzoate 25% 8 to 12 hrs once, crotramiton 10% 1 / day x 8 days and ivermectin 200 micrograms / kg in a single dose.